Finite element modeling of piezoelectric cantilever-beam energy harvester - L. V. Duong (Journal of Advanced Dielectrics)
Piezoelectric energy harvesting from mechanical vibrations has attracted considerable attention during the last decade. The homogeneous harvesters were studied experimentally or numerically by various models such as single degree of freedom (SDOF) modeling, finite element (FE) modeling as well as using analytical solutions. In this work, FE models for simulating a piezoelectric beam bimorph power harvester consisting of a laminated piezoelectric beam, a proof mass, and an electrical load (series or parallel connections) configurations are developed. The effects of the material and size of the substrate, the proof mass have been studied on the resonance frequencies and the output parameters of the piezoelectric generator (PEG). Numerical results obtained using the proposed procedure for piezoelectric bimorph power harvesters are in good agreement with the experimental data available in the literature. The proposed method can be used for modeling accurately this class of energy harvesting devices.